(untitled) (International journal of medical sciences, 2026)
The widespread use of modern digital technologies has significantly influenced children’s development. This article examines the concept of "digital autism" and its impact on children's psychological and cognitive development. Based on a review of scientific literature, the effects of screen time on speech development, attention span, and social interactions are analyzed. Additionally, recommendations for preventing digital autism are provided. The research findings indicate that excessive use of technology may lead to a decline in children's social communication skills, emotional detachment, and disruptions in developmental processes. Therefore, this article offers practical recommendations for parents, educators, and medical professionals.